THE EFFECTIVENESS OF THE PROSECUTOR'S AUTHORITY AS AN INVESTIGATOR OF ALLEGED CORRUPTION OFFENSES - Badaru, Baharuddin (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
This study aims to determine the effectiveness of the investigation into alleged corruption and the factors that influence the effectiveness of the investigation into alleged corruption. The research method used in writing this is an empirical method, with secondary and primary data coverage. The results of this study indicate that the effectiveness of the investigation into alleged corruption is still not effective, this can be seen from the existence of areas in investigations that have not been completed due to several obstacles in adjusting to the material elements of corruption and there are several factors that influence the effectiveness of the investigation into alleged corruption, including namely; legal substance, legal structure, facilities and infrastructure, and legal culture of the four factors that have the most influence on the effectiveness of the investigation of suspected corruption is the legal structure of calculations Auditor to BPK/BPKP. Recommendations for research on all forms of obstacles for the effectiveness of investigations into criminal acts of corruption committed by the investigating prosecutors so that they are even more efficient in finding evidence for the sake of accelerating investigations, increasing the number of prosecutors' personnel, and it is necessary to procure a new profession of prosecutors who are authorized in auditing (auditor certification), so that they have special expertise in financial auditing without Waiting too long for the audit results of other institutions for the sake of efficiency and acceleration of the next law enforcement process. Keywords: Investigative effectiveness, corruption.